Proyectos Energéticos en Salud: Oportunidad para la Mejora Continua - Hernandez Palma, Hugo Gaspar; Mendoza Casseres, Daniel; Duran Ravelo, Javier (Ingeniería, 2022)
Context: Climate change and the challenges faced by humanity in terms of sustainability encourage institutions in all sectors to take measures to reduce the impact of their activities. The purpose of the article is to analyze energy projects in the field of healthcare as an opportunity for continuous improvement. Method: A descriptive qualitative approach is employed to explore the recent literature on energy projects in healthcare. To this end, scientific articles published in the last five years in both English and Spanish were reviewed. Results: Energy management in healthcare institutions is present as an important component of global operations. However, there is still room for improvement in but in Latin America. 57% of green hospitals in Colombia have achieved energy sustainability goals, with the Cañaveralejo Hospital in the city of Cali being the main point of reference. Conclusions: Fundamental principles such as an ethical commitment to change, a self-management character, the participation and responsibility of the personnel involved, and the leadership and control of management are essential for achieving a successful change model.